Tax Planning and Compliance for Tax-Exempt Organizations, 6th Edition - Blazek, Jody (Wiley, 2020)
A practical guide to handling the challenges facing tax-exempt organizations, written by a leading authority Tax Planning and Compliance for Tax-Exempt Organizations, Sixth Edition ensures that you have the practical knowledge to handle critical tax situations. This book provides guidance for the significant issues facing nonprofit organizations. It's an essential guide to navigating the complexities of nonprofit tax rules and regulations. Packed with checklists and suggestions starting with Exhibit 1.1, Organizations Reference Chart and Exhibit 1.2, Suitability for Tax-Exempt Status , this guide helps anyone that creates, advises, or manages a nonprofit organization. Now, you can better understand the requirements for various categories of tax-exempt organizations: public charities, private foundations, civic associations, business leagues, and social clubs, as well as title-holding companies and governmental entities. You'll discover practical guidance on the issue of potentially owing income tax on revenue-producing enterprises. Clear explanations cover the many exceptions to taxability. Tax issues related to internet activity, advertising, publishing, services, and much more are all addressed in this tax planning guide designed specifically for nonprofit and tax-exempt nonprofit organizations. Use extensive quick checklists that cover tax-exempt eligibility, reporting to the IRS, and tax compliance Find detailed instructions for submitting a variety of exemption applications and tax forms See sample documents, such as organizational bylaws, letters of application, and completed IRS forms Refer to tools and practice aids, such as a comparison chart summarizing the differences between public and private charitable organizations Written by one of the leading authorities in the field, the book also delves into recent tax law changes affecting nonprofits and other tax-exempt organizations. This indispensable guide can offer direction and support if you are challenged to successfully navigate the complex maze of nonprofit tax rules and regulations.
Online resource; Title from title page (viewed April 28, 2020)
Keywords: Nonprofit organizations -- Taxation -- Law and legislation -- United States; Tax planning -- United States; Tax exemption -- Law and legislation -- United States; Planification fiscale; États-Unis; Tax planning; Tax exemption; Law and legislation; Nonprofit organizations; Taxation; Law and legislation; United States